Türkiye’de Büyük Merkezler Ölçeğinde Perakende Arazi Geliştirme Süreci : Örnek İncelemeleri - Öztürk, Aslı (Fen Bilimleri Enstitüsü, 2011)
With one foot in Europe and the other in Asia, Turkey is one of the great melting pots of peoples, cultures and religions. Turkey has an attractive, large population but a highly fragmented retail market and the urban society is increasing. There is a long-term potential for investment in the country. The purpose of the study is to examine the land development process on specific criterias, in order to conclude the subject of the differences of this process upon the growth scale of the cities. Especially the “large cities” are the focus of the work. Adapazarı, Denizli and Diyarbakır are the chosen countries varying for scales of large, middle and small due to the economical facts. There are selected cases located in Diyarbakır, Adapazarı and Denizli as shopping malls in order to compare the development process of their projects. In the last section of the thesis, conclusions and recommendations are provided upon these cases and the hypothesis verification is completed.

Türkiye, bir ayağı Avrupa, diğeri Asya’da bulunan bir ülke ve insanların, kültürlerin ve dinlerin erime potasıdır. Türkiye, çekici ve büyük bir nüfusa sahip olup, kentsel nüfusu artmakla birlikte oldukça eksik kalmış bir perakende pazarına sahiptir. Bu durum, ülkeyi uzun vadede oldukça potansiyel taşıyan bir konuma getirmektedir. Bu çalışmanın amacı, değişik şehir ölçekleri göz önünde bulundurularak, belirli kriterler kullanılarak arazi geliştirme süreçleri üzerinde ne gibi farklılıklar olduğunu ortaya koymaktır. İkincil merkezler bu çalışmanın amacı kapsamında özellikle seçilmiş ve değerlendirilmiştir. Adapazarı, Diyarbakır ve Denizli ekonomik özellikleri bakımından küçük, orta ve büyük ölçekli gelişim merkezleri olarak tespit edilmiştir. Diyarbakır, Adapazarı ve Denizli’de konumlu alışveriş merkezleri, projelerinin gelirştime aşamalarının kıyaslanabilmesi amacıyla seçilmiştir. Tezin son bölümünde bu incelemelere ilişkin sonuçlar, öneriler ve hipotez doğrulaması yapılmıştır.
Land Development Process In Large Cities Scale In Turkey : Case Examination
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2010
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2010
Keywords: land development process; retail land development; cost efficiency; case study; arazi geliştirme süreci; perakende arazi geliştirme; maliyet etkinliği; örnek incelemeleri